Teachers’ Perceptions of Quiz Maker: Enhancing Assessment Practices in Early Childhood Education - Putri, Winda Eka; Warmansyah, Jhoni; Nirwana, Evi Selva; Utami, Winda Trimelia (Journal of Childhood Development, 2025)
This study aims to examine teachers' perceptions of using the Quiz Maker application in the assessment of early childhood learning. A quantitative approach was employed using a survey method, with data collected through online questionnaires distributed to 52 kindergarten teachers in West Sumatra Province. The findings reveal that most teachers perceive Quiz Maker as a tool that simplifies and accelerates the assessment process, enhances evaluation effectiveness, and aids in understanding children’s development and thinking patterns. The application is also seen as supportive in improving teachers’ professionalism by enabling more accurate and efficient assessment practices. However, some teachers reported challenges related to technical understanding and the need for stable internet access. Concerns were also raised regarding the potential impact on children's social and emotional development if the application is not used in a balanced pedagogical approach. Despite these concerns, the majority of respondents still consider Quiz Maker a promising digital tool for early childhood education assessment, provided that its implementation is supported by adequate training and thoughtful integration into the learning process. This study contributes to the development of adaptive and child-friendly technology-based assessment practices in early childhood education.